Placental Vascular Calcification and Cardiovascular Health: It Is Time to Determine How Much of Maternal and Offspring Health Is Written in Stone - Wallingford, Mary C.; Benson, Ciara; Chavkin, Nicholas W.; Chin, Michael T.; Frasch, Martin G. (Frontiers in Physiology, 2018)
Vascular calcification is the deposition of calcium phosphate minerals in vascular tissue. Vascular calcification occurs by both active and passive processes. Extent and tissue-specific patterns of vascular calcification are predictors of cardiovascular morbidity and mortality. The placenta is a highly vascularized organ with specialized vasculature that mediates communication between two circulatory systems. At delivery the placenta often contains calcified tissue and calcification can be considered a marker of viral infection, but the mechanisms, histoanatomical specificity, and pathophysiological significance of placental calcification are poorly understood. In this review, we outline the current understanding of vascular calcification mechanisms, biomedical consequences, and therapeutic interventions in the context of histoanatomical types. We summarize available placental calcification data and clinical grading systems for placental calcification. We report on studies that have examined the association between placental calcification and acute adverse maternal and fetal outcomes. We then review the intersection between placental dysfunction and long-term cardiovascular health, including subsequent occurrence of maternal vascular calcification. Possible maternal phenotypes and trigger mechanisms that may predispose for calcification and cardiovascular disease are discussed. We go on to highlight the potential diagnostic value of placental calcification. Finally, we suggest avenues of research to evaluate placental calcification as a research model for investigating the relationship between placental dysfunction and cardiovascular health, as well as a biomarker for placental dysfunction, adverse clinical outcomes, and increased risk of subsequent maternal and offspring cardiovascular events.